Nanoparticle mucoadhesive system as a new tool for fish immune system modulation - Charlie-Silva, Ives; de Melo, Nathalie Ferreira Silva; Gomes, Juliana M.M.; Fraceto, Leonardo Fernandes [UNESP]; de Melo, Daniela Chemim; de Oliveira Silva, Juliana; de Barros, André Luis Branco; Corrêa, José Dias (Elsevier, 2018)
Recently, chitosan-based nanoparticles with mucoadhesive properties emerged as a strategy for mucosal drug release. This study aimed to characterize the interaction of mucoadhesive system chitosancoated PLGA nanoparticles (NPMA) with fish external mucus. NP suspensions with fluorescent probe were prepared and characterized by size, polydispersity, zeta potential and pH measures. In post-exposure fish were observed an increase in fluorescence imaging over time and it was significantly influenced by NPMA concentration. We also observed the main predominance the fluorescence in the spleen, followed by liver, gill and other tissues. The use of mucoadhesive nanocarriers becomes an alternative for administration of drugs and immunomodulators in immersion systems since the nanosystem can adhere to the mucosal surface of the fish with little residual effect in the water.
Keywords: Chitosan-coated PLGA nanoparticles; Immunomodulators; Mucoadhesive nanoparticles; Nanodelivery